The effect of infliximab dose escalation in inflammatory bowel disease patients with antibodies to infliximab. Issue 3 (March 2022) - Tun, Gloria S.Z.; Robinson, Kerry; Marshall, Laura; Wright, Alison; Thompson, Laura; Wild, Graeme; Sargur, Ravishankar; Brooks, Alenka J.; Hale, Melissa F.; Chew, Thean S.; Lobo, Alan J.
Abstract : Background: Infliximab dose escalation (DE) can be used in inflammatory bowel disease patient; however, the long-term benefit remains unclear, especially in those with antibodies to infliximab (ATI). The aim was to assess the effect of DE in patients with ATI on drug level, clinical response and ATI status. Methods: All patients undergoing infliximab DE (a reduction in dose interval between infusions <8 weeks ± an increase in dose up to 10 mg/kg) at a referral centre between April 2016 and August 2019 were included. Results: Ninety-two patients were DE: 51 were men, 50 had CD and 63 were receiving immunosuppression. A total of 87 people received DE for a median of 44 weeks (range 4–176). Five stopped infliximab after 1 dose of DE: 2 for loss of response and 3 for infusion reaction. In patients with ATI ⩽10 vs. >10 AU/mL, DE significantly increased drug levels: median infliximab levels of 1.4 and 0.9 at baseline, respectively, to 3.2 and 3.5 at week 24. After DE, 21/35 ATI-positive patients had a fall in ATI ⩽10 AU/mL. At week 24 following DE 62/92 patients were in clinical remission. Duration of clinical remission was shorter in those with ATI >10 AU/mL (median 24 weeks, range 0–88) than in those with transient/ATI ⩽10 AU/mL (median 36 weeks, range 0–126, P = 0.06). Conclusions: A strategy of DE for selected patients receiving infliximab is associated with an increase in drug levels and reduced ATI positivity. This is associated with clinical remission in approximately 70% of patients at 6 months.